2015
DOI: 10.1177/1071100715577195
|View full text |Cite
|
Sign up to set email alerts
|

High Rate of Recurrence Following Proximal Medial Opening Wedge Osteotomy for Correction of Moderate Hallux Valgus

Abstract: Level IV, retrospective case series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 19 publications
0
29
1
Order By: Relevance
“…What is more, the majority of the published studies presented outcome after linear distal metatarsal osteotomies [ 14 ], which might have an impact on the joint line. Iyer et al found higher recurrence rates in individuals with pathological joint lines, whereas another study demonstrated a probability for a metatarsal misload after Reverdin-Isham procedures [ 26 , 27 ]. Other authors showed already good clinical and radiological results with a minimally invasive chevron technique, but our analysis is the first to compare a minimally invasive chevron type and an open chevron osteotomy in a randomized manner [ 9 , 10 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…What is more, the majority of the published studies presented outcome after linear distal metatarsal osteotomies [ 14 ], which might have an impact on the joint line. Iyer et al found higher recurrence rates in individuals with pathological joint lines, whereas another study demonstrated a probability for a metatarsal misload after Reverdin-Isham procedures [ 26 , 27 ]. Other authors showed already good clinical and radiological results with a minimally invasive chevron technique, but our analysis is the first to compare a minimally invasive chevron type and an open chevron osteotomy in a randomized manner [ 9 , 10 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because MPV is the product of failed ligaments and a destabilized first metatarsal, its restabilization is just as important as its realignment (14). Restoration of first metatarsal stability has been sufficiently discussed and understood; however, the recurrence of the MPV deformity remains mostly unresolved (15,16). Although arthrodesis of the metatarsocuneiform joint using the Lapidus procedure has thus been recommended to help prevent recurrence (9), recurrence can still develop (17).…”
mentioning
confidence: 99%
“…Reasons for poor outcomes can be multifactorial, and these risk factors can interact with each other to complicate matters. 9 For example, a high preoperative hallux valgus angle is associated with recurrence of hallux valgus deformity 10 while it has also been shown that the metatarsus adductus angle is associated with the hallux valgus angle. 11,12 The goal of this study is to observe the relationship between underlying metatarsus adductus deformity and the outcomes of hallux valgus corrective procedures, while adjusting for other covariates.…”
mentioning
confidence: 99%